Node Importance Measurement Method in Heterogeneous Information Satellite Network - Jingling Li; Jun Li; Wei Liang; Tao Cui; Yi Zhang (天地一体化信息网络)
In satellite network, different nodes have different effects on network connectivity and throughput.In order to avoid network communication disturbances caused by the failure of key nodes in the satellite network, network planning can be carried out in advance by measuring the importance of satellite network nodes.According to the characteristics of satellite network information heterogeneity, satellite virtual nodes and virtual sub-layers were defined, and the satellite multi-layer heterogeneous information correlation network model was proposed.The normalized degree, normalized node betweenness and virtual node correlation factor of virtual nodes were defi ned, and the network node importance calculation function was proposed through the defined parameters, which could accurately measured the node importance in the satellite multi-layer heterogeneous information network.Based on typical examples, the network connectivity and throughput indicators were analyzed.The results showed that the proposed algorithm was better than the classical graph theory algorithm, which could comprehensively considered the impact of data information on the importance of network nodes, and more accurately described the connectivity index of satellite multi-layer heterogeneous information networks.